Produksi kompos dari aneka limbah jagung - Syamsia Syamsia; Abubakar Idhan; Kasifah Kasifah (Unri Conference Series: Community Engagement, 2019)
PPUPIK Business Unit Muhammadiyah University Certified Plant Seed Production Center Makassar is a science and technology-based business unit that aims to develop campus entrepreneurship based on research results. The main product of this business unit is hybrid corn seeds, but in the process of producing corn seeds in addition to producing economically valuable corn seeds also produce corn waste which can cause problems if not handled. PPUPIK developed various waste corn compost products for the development of new business units. The production activities of various corn waste into compost products aim to make corn waste as a product of economic value and also as a place of practice for students in the application of science and technology and science-based entrepreneurial activities. The method of implementing the activity is divided into 5 stages, namely: 1) Production of various waste corn compost; 2) Analysis of nutrient content of compost; 3) Product label design; 4) Compost packaging; 5) Promotion and marketing of products. This activity involved students of the Faculty of Agriculture, the University of Muhammadiyah Makassar in the production, label design and promotion and marketing of products. The results obtained from this activity include; 1) students have experience in compost production, label design and product promotion and marketing; 2) the formation of a new business unit in PPUPIK activities; 3) produce economic value products from waste; 4) potential to get IPR.